2003
DOI: 10.1385/mo:20:1:87
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival of Patients Given Hormonal Therapy for Metastatic Endometrial Stromal Sarcoma

Abstract: Endometrial stromal sarcoma (ESS) is a rare neoplasm, mainly observed in premenopausal women. We describe two women 44 and 34 years old at the time ESS diagnosis, who developed lung metastases 3 and 6 years, respectively, after initial treatment: hysterectomy without (case 1) or with oophorectomy (case 2), followed by hormone replacement therapy (HRT) for the latter. Their estrogen (ER) and progesterone receptors (PR) were analyzed biochemically in metastatic lung tissue, yielding respective concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 16 publications
0
58
0
1
Order By: Relevance
“…24,25 The demonstration of aromatase expression in low-grade endometrial stromal sarcomas may be a rationale for a study of aromatase inhibitors in the treatment of women with lowgrade endometrial stromal sarcomas. Spano et al 26 have reported initial results of such adjuvant hormonal therapy. In their series, two patients with metastatic low-grade endometrial stromal sarcomas had a complete response after treatment with an aromatase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The demonstration of aromatase expression in low-grade endometrial stromal sarcomas may be a rationale for a study of aromatase inhibitors in the treatment of women with lowgrade endometrial stromal sarcomas. Spano et al 26 have reported initial results of such adjuvant hormonal therapy. In their series, two patients with metastatic low-grade endometrial stromal sarcomas had a complete response after treatment with an aromatase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Hormone therapy include: a) megestrol/medroxyprogesterone, gonadotrophin releasing hormone analogues and aromatase inhibitors, like letrazole and anastrozole. Spano JP et al [6] and Alkasi et al [7], are 2 case reports which shows 10 year free survival rate for the patients that received aromatase inhibitor for 10 years. Chu et al [8], study compared the outcome for the patients who received adjuvant megestrol 160mg/day with those who didn't.…”
Section: Treatmentmentioning
confidence: 99%
“…Data on the efficacy of AIs for ESS are scarce, with most published studies being case reports [23][24][25][26][27][28][29][30]. There is a report of complete responses lasting for more than 7 and 14 years in two patients with lung metastases treated with aminoglutethimide (500 mg bid) [28].…”
Section: Endocrine Therapymentioning
confidence: 99%
“…There is a report of complete responses lasting for more than 7 and 14 years in two patients with lung metastases treated with aminoglutethimide (500 mg bid) [28]. Another study reported two year disease stabilization in ESS with sex-cord compound, treated with anastrozole and megestrol acetate [25].…”
Section: Endocrine Therapymentioning
confidence: 99%